Atomic spectrometry update: review of advances in the analysis of clinical and biological materials, foods and beverages. Issue 3 (28th February 2020) - Taylor, Andrew; Catchpole, Anthony; Day, Martin P.; Hill, Sarah; Martin, Nicholas; Patriarca, Marina
Abstract : This review discusses developments in elemental mass spectrometry, atomic absorption, emission and fluorescence, XRF and LIBS, as applied to the analysis of specimens of clinical interest, foods and beverages. Sample preparation procedures and quality assurance are also included. Abstract : This update covers publications from the second half of 2017 to the middle of 2019. Techniques and applications relevant to clinical and biological materials, foods and beverages are discussed in the text, presenting key aspects of the work referenced, while the tables provide a summary of the publications considered. A tutorial review gives an encyclopaedic account of how ICP-MS has developed for analysis of metal-containing nanoparticles and colloids. While it is a relatively new area, interest in how LIBS has many clinical applications is such that this topic is expertly reviewed. As previously noted in recent Updates, the growing importance of XRF techniques is accompanied by useful review papers. Among the technical developments that featured during the year were yet more materials for preconcentration or speciation, a high-temperature torch as part of a novel integrated ICP-MS sample introduction system, and a tubular dielectric barrier discharge trap as an alternative to vapour traps such as quartz tube or graphite furnace, all of which lead to lower claimed detection limits. A new approach to imaging applications, offered by ICP-TOF-MS, also provides for lower LODs. Measurements of As and Hg continue to feature heavily in work with foods and beverages. Of note, is a collaborative project to validate a straightforward HG-ICP-MS procedure in view of anticipated EU legislation on the maximum allowable limits of iHg in marine samples. Several articles concerning trace elements and fertility and reproductive health were noted during this review period with publications focusing on single, or groups of elements, in maternal blood, follicular fluid, placental tissue, and progress of pregnancy. Two accounts describe unusual incidents of poisoning. Cigarettes, adulterated with Hg, were provided to the victim. Flu-like symptoms developed after smoking. A dog developed symptoms of Ba poisoning after eating a firework, it made a complete recovery, with prompt treatment. Results from population studies can sometimes produce ambiguous results but the levels of 13 elements in urine from healthy Italian adults look realistic.